The renal effects of nonsteroidal anti-inflammatory drugs (NSAIDS) in dogs with chronic kidney disease (CKD) - Lomas, Amy (Kansas State University, 2013)
Prostaglandins play many important roles in the kidney including regulation of renal blood flow, glomerular filtration, renin release, and sodium excretion. Upon activation of the renin angiotensin aldosterone system (RAAS), prostaglandin upregulation becomes critical to offset the vasoconstrictive effects of norephinephrine, angiotensin II, and vasopressin. Nonsteroidal anti-inflammatory drugs (NSAIDs) produce both their beneficial and detrimental effects through inhibition of the cyclooxygenase enzyme and subsequent interference with prostaglandin production. Healthy canine kidneys express both COX-1 and COX-2, although basal COX-2 expression in dogs is significantly higher than in other species. Nonsteroidal anti-inflammatory drugs that spare COX-1 have exhibited less gastrointestinal toxicity, but no NSAID has been proven safe for the kidney. The kidney is the organ with the second highest reports of adverse drug events, which is usually manifested as functional changes. However, structural changes including renal papillary necrosis, can occasionally be observed. Dogs with chronic kidney disease could be expected to be at increased risk for NSAID-related adverse drug effects. As nephrons and renal reserve are lost in chronic kidney disease, the canine kidney becomes more dependent on COX-2 for production of prostaglandins. Inasmuch as the prevalence of both CKD and OA increases with age, it is expected that many dogs being treated with NSAIDs for OA will have loss of renal reserve and/or early stage CKD. If administration of an NSAID is required for long term treatment of osteoarthritis, frequent monitoring of blood pressure and renal parameters, as well as hepatic enzymes are recommended.
Keywords: Chronic kidney disease; Canine; Osteoarthritis; Non-steroidal anti-inflammatory drugs; Adverse drug events; Veterinary Medicine (0778)